Analisis Electronic Word Of Mouth (eWOM) Terhadap Brand Image, Brand Trust, dan Minat Beli Pada Smartphone iPhone (Studi Pada Mahasiswa Prodi Manajemen FEB UNISMA Angkatan 2018) - Wahyu Setiaji; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to examine and explain the effect of electronic word of mouth, on interest in buying Smartphone Iphones which is mediated by brand image, and brand trust, both direct and indirect influences study FEB Unisma students. This research is an explanatory research type with a quantitative approach. The method used is study the Preacher & Hayes approach, which is the recommended method using the bootstrapping technique.. The sampling technique used the formula from Malhotra with the calculation results of 80 samples. To solve the problem in this study using SPSS assistance with validity test, reliability test, normality test, path analysis. The results in this study indicate that the eWOM variable has a direct effect on the brand image and brand trust of the Iphone Smartphone. However, eWOM does not directly affect buying interest. Although the indirect effect or mediation effect is said to be proven if there is a direct relationship between the eWOM variable on buying interest, but based on the results in this study there is no direct relationship between eWOM and buying interest, it can be concluded that there is an indirect relationship between eWOM and buying interest. through brand image and brand trust, it is indicated that there is no mediating effect. Keywords: electronic word of mouth, brand image, brand trust, and purchase intention